Things Japanese : - Chamberlain, Basil Hall (John murray, 1905)
In the unlikely event of any one instituting a minute comparison between this edition and its predecessor, he would find minor alterations innumerable,--here a line erased, there a paragraph added, or again a figure changed, a statement qualified, a description or a list brought up to date. But take it altogether, the book remains the same as heretofore. It would seem to have found favour in many quarters, to judge from the manner in which, years after its first appearance, newspapers and book-makers continue to quote wholesale from it without acknowledgment; and the title, which cost us much cogitation, and which we borrowed ultimately from the Spanish phrase cosas de España, has passed into general use, even coming to supply titles for similar works written about other lands in imitation of this one